2021
DOI: 10.1152/jn.00067.2021
|View full text |Cite
|
Sign up to set email alerts
|

Role of olfactory receptor78 in carotid body-dependent sympathetic activation and hypertension in murine models of chronic intermittent hypoxia

Abstract: Chronic intermittent hypoxia (CIH) is a hallmark manifestation of obstructive sleep apnea (OSA), a widespread breathing disorder. CIH treated rodents exhibit activation of the sympathetic nervous system and hypertension. Heightened carotid body (CB) activity has been implicated in CIH-induced hypertension. CB expresses high abundance of olfactory receptor (Olfr) 78, a G-protein coupled receptor. Olfr 78 null mice exhibit impaired CB sensory nerve response to acute hypoxia. Present study examined whether Olfr78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…While it is not possible to perfectly mimic OSA by exposing mice or cells to IH exposure, our published data, measuring blood gases, and other reference points support the use of in vitro and in vivo models of IH that we employed in our studies ( Peng and Prabhakar, 2003 , 2004 ). We did not measure blood pressure in the current study as an endpoint to determine whether mice were exposed equally to IH; however, we have recently reported blood pressure responses to IH in non-sedated mice using tail-cuff method as well as a telemetry approach ( Peng et al, 2006 , 2021 ). Both approaches showed significant elevation of both systolic and diastolic blood pressure in C57BL/6 mice treated with IH for 10 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is not possible to perfectly mimic OSA by exposing mice or cells to IH exposure, our published data, measuring blood gases, and other reference points support the use of in vitro and in vivo models of IH that we employed in our studies ( Peng and Prabhakar, 2003 , 2004 ). We did not measure blood pressure in the current study as an endpoint to determine whether mice were exposed equally to IH; however, we have recently reported blood pressure responses to IH in non-sedated mice using tail-cuff method as well as a telemetry approach ( Peng et al, 2006 , 2021 ). Both approaches showed significant elevation of both systolic and diastolic blood pressure in C57BL/6 mice treated with IH for 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, OSA is characterized by collapse of the upper airway causing recurrent pauses in breathing during sleep leading to intermittent hypoxemia (IH), arousals, changes in intrathoracic pressure, and sleep fragmentation ( Somers et al, 1995 ; Gabryelska et al, 2018 ). Furthermore, patients with OSA exhibit increased sympathetic nerve activity ( Dempsey et al, 2010 ; Prabhakar, 2016 ) as well as elevated circulating and urinary catecholamines (both norepinephrine and epinephrine), which are attributed to heightened sympathetic nerve activity ( Fletcher et al, 1987 ; Carlson et al, 1993 ; Marrone et al, 1993 ; Somers et al, 1995 ; Peng et al, 2021 ). IH is a hallmark manifestation of OSA and thought to be a major factor contributing to the pathogenesis of OSA-related cardiovascular morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we concluded that at least some oxytocin neurons expressed Olfr78. Previous reports have demonstrated that Olfr78 is expressed in cells with chemosensory properties[ 3 , 5 , 6 , 9 ]. Olfr78 responds to various small fatty acids, while the endogenous ligand for Olfr78 remains undetermined [ 4 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their extraolfactory expression has been intensively investigated and is increasingly reported. One olfactory receptor superfamily member, olfactory receptor 78 (Olfr78), is widely expressed, for example, in the brain [ 1 ] kidney [ 2 ], arterioles [ 3 , 4 ], carotid body [ 5 ], macrophages [ 6 ], colon [ 7 ], and prostate [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation